2016
DOI: 10.12965/jer.1632660.330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of startup circuit exercise on derivatives reactive oxygen metabolites, biological antioxidant potential levels and physical fitness of adolescents boys with intellectual disabilities

Abstract: The purpose of this study was to examine the effect of starup circuit exercise program on derivatives reactive oxygen metabolite (d-ROM) and biological antioxidant potential (BAP) levels and physical fitness of adolescents with intellectual disabilities, and to sugesst exercise programs to promote the health and physical development of such adolescents. Twelve students with intellectual disabilities were divided into two groups; circuit exercise group (CE group: n=6; age, 14.83±0.98 years; height, 163.83±5.78 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Youths with IDs in the present study were discovered to have significant improvements in physical fitness components, namely cardiorespiratory fitness and abdominal strength and endurance, after the 12-week floor hockey intervention ( Table 4 and Figure 2 ). Findings accord with several intervention studies on youths with IDs and typically developing youths that have revealed positive effects of PA interventions on several physical fitness outcomes in this population [ 13 , 37 , 38 , 60 , 63 , 64 ]. These improvements in the physical fitness of the participants with IDs may be attributable to improvements in motor proficiency due to increases in PA (i.e., floor hockey training).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Youths with IDs in the present study were discovered to have significant improvements in physical fitness components, namely cardiorespiratory fitness and abdominal strength and endurance, after the 12-week floor hockey intervention ( Table 4 and Figure 2 ). Findings accord with several intervention studies on youths with IDs and typically developing youths that have revealed positive effects of PA interventions on several physical fitness outcomes in this population [ 13 , 37 , 38 , 60 , 63 , 64 ]. These improvements in the physical fitness of the participants with IDs may be attributable to improvements in motor proficiency due to increases in PA (i.e., floor hockey training).…”
Section: Discussionsupporting
confidence: 86%
“…Two studies conducted in Asia on samples of more than 400 youths with IDs identified significant correlations of motor proficiency with muscular strength and endurance and cardiorespiratory fitness [ 65 , 66 ]. The positive findings of the current study echo those of early studies [ 13 , 37 , 38 , 60 , 63 ], synthesizing evidence regarding the effects of PA training on physical fitness levels in youths with IDs. Our results also extend the findings of these early studies by indicating that floor hockey practice can improve not only physical fitness but also other motor proficiency and adaptive functioning outcomes among youths with IDs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…When participants showed excessive facility for performing exercises, they were transferred to the next intensity-group. CO: Typical programming TX: 25 min sessions 2×/wk 21 wks Unspecified TX: Investigator and assistants CO: NR Pre and post 21-wk intervention Fat Mass Group x Time interaction NS NR Weak Lean Mass Significant Group x Time interaction (p=.027) in favor of TX NR Kim & Lee, 2016 RCT n=12 children 14-16 yrs, M=14.9 (TX) 15 (CO) 100% Male Race/Ethnicity: NR Primary diagnosis: ID TX: Circuit exercise program – warm-up and stretching; progression from 4 to 6 circuits including three strength exercise (elastic-band exercise and medicine ball exercise) and two cardiovascular exercises (side-step, jumping jack); cool down CO: Typical programming TX: 40 min sessions 4×/wk 12 wks Unspecified TX: Investigator and instructor CO: NR Pre and post 12-wk intervention Body fat % Significant Group x Time interaction (p=.026) in favor of TX Small* Weak Kocić et al, 2017 Quasi n=50 children Age Range NR, M=15.7 (TX) 15.9 (CO) 54% Male; 46% Female Race/Ethnicity: NR Primary diagnosis: Mild ID TX: Adapted basketball training focusing on ball handling, reception, passing, and shooting CO: Typical Programming TX: 25-35 min sessions 4×/wk 8 wks Unspecified TX: Investigators CO: NR Pre and post 8-wk intervention Body Fat (bioelectrical impedance) NS difference b/w TX and CO NR Weak Cardiovascular Fitness – Resting HR NS difference b/w TX and CO NR Cardiovascular Fitness – HR during 6MWT NS difference b/w TX and CO NR Cardiorespiratory Fitness – 6MWT, distance Significant difference in degree of change in favor of TX (p<.05) NR Kong et al, 2019 Quasi n=53 children 10-18 yrs, M=14.9 yrs 84.9% Male; 15.1% Female Race/Ethnicity: 100% Asian Primary diagnosis: ID without Down Syndrome TX1: Customiz...…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies (Boer et al, 2014 ; Elmahgoub et al, 2011 ; George et al, 2011 ; González-Agüero et al, 2011 ; Kim & Lee, 2016 ; Kong et al, 2019 ; Seron et al, 2014 ; Wu et al, 2017 ; Xu et al, 2020 ) focused on promoting physical activity through aerobic and/or strength training exercise programs. These interventions comprised a defined exercise regimen performed under the supervision of qualified trainers including physical therapists, physical therapy students, certified physical educators or personal trainers, and a Tai Chi master.…”
Section: Resultsmentioning
confidence: 99%